Penerapan Prinsip-Prinsip Good Corporate Governance pada Program Corporate Social Responsibility - Nur Asiah; Sri Haryanti; Zulkarnain Zulkarnain (Institut Manajemen Wiyata Indonesia, 2020)
This research discusses the application of the principles of GCG through the CSR program and tries to examine the various policies applied in various countries in implementing CSR as an illustration for Indonesia in implementing policies so that CSR can be focused and directed. The research was conducted using a literature review approach. Literature search through an online search engine from the Google Scholar database, Directory of Open Access Journals (DOAJ), Elsevier, and Wiley Online Library. The conclusion from the results of this study is that Indonesia is right to use a mandatory system, if CSR is only based on voluntary principles, this certainly cannot be carried out effectively and measurably in the application of CSR. CSR should have binding legal force and legal certainty as well as an obligation that must be carried out by the company. The obligation that must be carried out by the company is in the form of an obligation to issue the results of CSR activity reports to the public. In addition, it needs an important first step in implementing GCG, the Indonesian government can form a special agency or institution that is tasked with implementing the concept of GCG and implementing CSR in Indonesia. So, it is hoped that the implementation of CSR will be more focused and focused.